Preserving DNA in Biodegradable Organosilica Encapsulates - Koch, Julian; Kerl, Ann-Christin; Schawalder, Natascha; Luescher, Anne M.; Nguyen, Bichlien; Strauss, Karin; Stark, Wendelin J.; Grass, Robert N. (Langmuir, 2022)
A core–shell strategy was developed to protect synthetic DNA in organosilica particles encompassing dithiol linkages allowing for a DNA loading of 1.1 wt %. DNA stability tests involving bleach as an oxidant showed that following the procedure DNA was sandwiched between core particles of ca. 450 nm size and a protective outer layer, separating the DNA from the environment. Rapid aging tests at 60 °C and 50% relative humidity revealed that the DNA protected within this material was significantly more stable than nonprotected DNA, with an expected ambient temperature half-life of over 60 years. Still, and due to the presence of the dithiol linkages in the backbone of the organosilica material, the particles degraded in the presence of reducing agents (TCEP and glutathione) and disintegrated within several days in a simulated compost environment, which was employed to test the biodegradability of the material. This is in contrast to DNA encapsulated following state of the art procedures in pure SiO2 particles, which do not biodegrade in the investigated timeframes and conditions. The results show that synthetic DNA protected within dithiol comprising organosilica particles presents a strategy to store digital data at a high storage capacity for long time frames in a fully biodegradable format.